Uncommon presentation of methotrexate-induced toxic erythema of chemotherapy - Preema Sinha; Sunmeet Sandhu; Rohit Kothari; Shekhar Neema (Wolters Kluwer Medknow Publications, 2021)
Toxic erythema of chemotherapy (TEC) is a term used to describe the presence of erythema with or without edema often affecting the hands and feet, intertriginous areas such as axillary and inguinal areas and less frequently elbows, knees, and postauricular areas. Sometimes the lesions can be petechial or with sterile blisters. They are generally self-limiting and resolve with post-inflammatory hyperpigmentation. Here we describe one such rare case of Methotrexate-induced TEC involving uncommon sites like hairline, postauricular areas, and neck.